Limited evidence that tropical inundation and precipitation powered the 2020–2022 methane surge - Ying Xiong; Eric A. Kort; A. Anthony Bloom; Cynthia Gerlein-Safdi; Tianjiao Pu; Eren Bilir (Communications Earth & Environment)
Abstract Atmospheric methane is rapidly increasing, and the role of tropical wetlands in the global methane budget raises concerns about a potential climate-wetland-methane feedback. Here we use Cyclone Global Navigation Satellite System observations to map monthly inundation dynamics across the tropics (37.4°S to 37.4°N) at high resolution (0.01° × 0.01°) over five years (2018–2023), including cloud and vegetation-covered regions. Our results reveal large seasonal and interannual variations in wetland extent not captured in traditional inundation products, with strong El Niño-Southern Oscillation correlations. Tropical wetland models driven by these inundation observations, independent precipitation products, or constrained by total water observations do not show growth in wetland methane emissions from 2020–2022. This suggests the 2020–2022 growth in methane is best explained by other methane source or sink mechanisms, or that non-hydrological controls are more important in tropical wetland methane emissions than currently understood.